The effect of soil cultivation methods with different machine on planting success in arid and semi-arid area aforestations - Süleyman GÜLCÜ; İsmail ÇELİK (Turkish Journal of Forestry, 2016)
In this study which analyzes the effect of different tillage methods on planting success in arid and semi-arid area forestations, 12 different processes were tested. Within this scope, deep subsurface tillage in full range with double and triple ripper, top soil tillage with light and heavy disk harrow and gradoni type terrace making with two furrow plough processes were applied either singly or combined. In plantings, containerized seedlings of Black Pine, Taurus Cedar and Crimean Juniper were used. The experiment was laid out as completely randomized plot design with 3 replications in Karaman/Ayrancı region. At the end of first and second vegetation periods after planting, survival percent, sapling height, elongation of the terminal shoot and basal diameter measurements were done. Data were evaluated in SPSS statistics package program. According to Variance Analysis and Duncan test results, among processes taken to experiment, processes no 2 (double riper+gradoni terrace) and no 8 (triple riper+gradoni terrace) were included in the most successful five or six process and suggested for all three species thinking that it would be economic and enable application easiness. According to survival percent results obtained at the end of first and two vegetation processes, first of all Crimean Juniper and Taurus Cedar can be preferred in forestation in and around the experiment area due to high survival percent. Although Black pine has given 43% of survival percent as of the second year, considering its natural propagation, biological and silvicultural characteristics, it should absolutely be planted in forestation of arid and semi-arid areas.